Sistem dan Prosedur Pengendalian Internal Pemberian Kredit pada UED SP Desa Tanah Merah, Siak Hulu, Kampar - Febdwi Suryani (COSTING : Journal of Economic, Business and Accounting, 2017)
This study aims to analyze the internal control system and procedures of lending activities in UEDSP Desa Tanah Merah Kecamatan Siak Hulu Kabupaten Kampar. Internal control of lending activities to an organizations is one important aspect. Data resources used in this study are from interview and questionnaires by the UEDSP managers and the datas were analyzed by descriptive method and sign test. The result found that internal control of lending activities of UED SP Desa Tanah Merah has been running effectively in organizational structure, authorization system and recording procedures, healthy practices and qualified management. Keywords: Internal Control System and Procedure, Lending Activities